Forecasting Urban Expansion in the Seven Lakes Area in San Pablo City, Laguna, the Philippines Using the Land Transformation Model - Quintal, Anna Laura (Archīum Ateneo, 2018)
Managing urban growth is essential to the conservation of the Seven Lakes ecosystem in San Pablo City, Laguna province in the Philippines. This study simulates potential conversion of agricultural lands to built-up areas using the land transformation model (LTM), which integrates geographical information systems (GIS) and an artificial neural network (ANN). Historical drivers of the expansion of built-up areas are identified and validated through the application of LTM to land cover maps from 1988 to 2015. Identified drivers include distance to roads, distance to trails, distance to the Seven Lakes, distance to existing built-up areas, slopes and population density per barangay. Results from the percent correct matrix (PCM) were 79.88 per cent for the 1988–2003 runs and 66.42 per cent for the 2003–2015 runs, while the Kappa statistic for both time periods was higher than 0.60, which indicates high levels of agreement. Forecasted scenarios were business-as-usual (BAU) growth, doubled growth and strict law implementation protecting the vicinity around the Seven Lakes and other natural areas. In the BAU scenario, urban expansion spread out along the road networks. The doubled growth scenario showed that further expansion will likely extend around the proximity of the lakes, which may adversely affect the livelihoods of the local fishing communities. As such, it was recommended that preventive measures, such as strict implementation of buffer zones coupled with regular monitoring, be taken to manage land use in the surrounding lake areas.